Perencanaan Strategi Perusahaan Dalam Menghaapi Persaingan Bisnis - Budiman Budiman; Zulkifli Zulkifli; Derriawan Derriawan (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
This research is a qualitative research that aims to formulate and plan a strategy for PT Swadharma Sarana Informatika and also to formulate and determine the selection of a business strategy at PT Swadharma Sarana Informatika. The results of the research are expected to provide guidelines for strategic planning for companies that can be used as procedures for writing a scientific research. The results of the research are formulating strategies that are obtained are market penetration strategies and product development strategies and also alternative strategies, namely Education and Training.